Drug treatment of primary hyperparathyroidism: use of clodronate disodium. Issue 6365 (19th February 1983) - Douglas, D L; Kanis, J A; Paterson, A D; Beard, D J; Cameron, E C; Watson, M E; Woodhead, S; Williams, J; Russell, R G
Abstract : Clodronate disodium (dichloromethylene diphosphonate), a specific inhibitor of bone resorption, was given by mouth (1.0-3.2 g daily) to nine patients with primary hyperparathyroidism for two to 32 weeks so that its clinical and metabolic effects could be evaluated. Bone resorption decreased in all patients as judged by a fall in the fasting urinary calcium to creatinine and hydroxyproline to creatinine ratios. Serum calcium concentration was increased in all patients before treatment and fell in response to treatment to values near the upper end of the normal range. Hypercalcaemia and hypercalciuria recurred when treatment was stopped. In three patients treated for longer than 19 weeks clodronate failed to sustain the reduction in serum calcium concentration but the concentration remained below pretreatment values. These results suggest that clodronate may be of use in the medical management of primary hyperparathyroidism, particularly in patients in whom suppression of bone disease is desirable before surgery or in whom surgery is contraindicated.